MEMBANGUN KARAKTER ISLAMI: PEMBIASAAN MEMBACA ASMAUL HUSNA DAN AYAT AL-QUR'AN SEBELUM PEMBELAJARAN DIMULAI DI SMAN 2 KLARI - Tia Febbiyanti; Heri Sandi; Tiara Safitri; Siti Masruroh; Ainur Alam Budi Utomo (STKIP Subang, 2026)
This study aims to develop Islamic character among students through the habit of reading Asmaul Husna and verses of the Qur'an before learning begins at SMAN 2 Klari. This program is designed to integrate spiritual values into school routines in order to improve students' morals, discipline, and religious awareness. The method used in this study is qualitative descriptive, with data collection through observation, interviews, and documentation. The results of the study indicate that this habit is able to create a more conducive learning atmosphere, improve discipline, and strengthen students' religiosity aspects. In addition, this habit also acts as a medium for strengthening Islamic character, such as patience, honesty, and a sense of responsibility. The implementation of this program requires support from the school, teachers, and parents so that it can take place consistently and sustainably. This study concludes that the habit of reading Asmaul Husna and verses of the Qur'an before learning is a strategic step in building a generation with Islamic character.